Synthesis of highly sulfonated polyarylene ethers containing alternating aromatic units. (June 2015) - Lee, Hsu-Feng; Huang, Yi-Chiang; Wang, Po-Hsun; Lee, Chun Che; Hung, Yi-Syuan; Gopal, Ram; Holdcroft, Steven; Huang, Wen-Yao
Graphical abstract: Sulfonated multi-phenylated alternating copolymers were synthesized. The strategy of using highly-encumbered polymer frameworks for the design of mechanically-robust and dimensionally-stable proton conducting membranes is demonstrated. Proton conductivities ranged between 0.08 and 0.26 S/cm at 80 °C/95% RH. TEM analysis of the polymers, in the dehydrated state, revealed isolated spherical aggregates of ions, which coalesce upon hydration to provide highly conductive pathways. Abstract: Sulfonated, sterically-encumbered, alternating copolymers based on poly(arylene ether) are reported. The polymers were prepared by polymerization of 9, 9-bis(4-hydroxyphenyl) fluorene with a novel monomer, 4, 4⁗-difluoro-3, 3⁗-bistrifluoromethyl-2″, 3″, 5″, 6″-tetraphenyl-[1, 1′;4′, 1″;4″, 1‴;4‴, 1⁗]-pentaphenyl. Subsequent sulfonation and solution casting provided membranes possessing ion exchange capacities ranging from 0.5 to 2.7 mmol/g. Proton conductivities of membranes increased with IEC and temperature to values > 260 mS/cm (at 80 °C, 95% RH). The membranes exhibited good dimensional stability upon water sorption and a resistance to swelling. Dry membranes comprised of isolated spherical aggregates of ions, which upon hydration formed highly conductive pathways, as visualized by AFM analysis. We infer that introducing a high free volume into the polymer by way of incorporating highly sulfonated, multi-phenylated moieties provides mechanically-robust and dimensionally-stable proton exchange membranes.